User Adoption and benefit of Single Identity Number (Empirical Study from Directorate General of Tax) - Kusumadewi Sumarna, Merry; Gunawan, Andri; Fredy Maradona, Agus (Dinasti Publisher, 2024)
The purpose of this research is to analyze the variables affecting user adoption of the Single Identity Number and the benefits derived from it. The adoption variables include user convenience, social influence, performance expectancy, facilitating conditions, trust in the internet, trust in the government, and societal culture. The benefit variables were taxpayer compliance, tax revenue, and public satisfaction. This quantitative study used incidental sampling for sample collection and used Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS) statistical methods. The results of this study indicate that user convenience, social influence, performance expectancy, facilitating conditions, trust in the internet, trust in the government, and societal culture have a significant positive effect on the intention to integrate NIK (National Identity Number) and NPWP (Taxpayer Identification Number). Furthermore, the intention to integrate NIK and NPWP has a significant positive impact on the intention to pay taxes, tax compliance and public satisfaction.